Berries containing anthocyanins with enhanced methylation profiles are more effective at ameliorating high fat diet-induced metabolic damage. (January 2018) - Skates, Emily; Overall, John; DeZego, Katelyn; Wilson, Mickey; Esposito, Debora; Lila, Mary Ann; Komarnytsky, Slavko
Abstract: Driven by the need for alternative whole food options to manage metabolic syndrome, multiple dietary interventions are suggested to achieve a better control of metabolic risk factors and molecular networks that regulate cellular energy metabolism. It is generally accepted that anthocyanin-rich diets are beneficial for maintaining healthy body weight, improving glucose and lipid metabolism, and determining inflammatory status of key metabolic tissues. However, anthocyanins are a structurally diverse group of phenolic compounds and their individual contributions to improving metabolic health are not clear. In this study, we show that consumption of berries containing anthocyanins with enhanced methylation profiles (malvidin and petunidin) is more effective at reducing high fat diet-induced metabolic damage in the C57BL/6 mouse model of polygenic obesity. Blueberries and Concord grapes (57% and 33% anthocyanins as malvidin, petunidin, or peonidin, respectively) improved body composition through individual significant effects on energy expenditure and increased activity. Methylated anthocyanins are also more effective at enhancing mitochondrial respiration and dissipation of the mitochondrial proton gradient (proton leak) in adipose tissue, thus counteracting mitochondrial dysfunction associated with metabolic stress. Together, these results provide direct proof of the higher protective potential of methylated anthocyanins against the metabolic consequences of chronic exposure to calorie-dense foods. Graphical abstract: Highlights: Berry supplementation alleviated high fat diet-induced metabolic damage. Anthocyanins with enhanced methylation profiles were more effective. Blueberries and Concord grape improved body composition and energy expenditure. Methylated anthocyanins increased oxidative phosphorylation, but decreased overall mitochondrial coupling efficiency.